The Control using More Rigid Control Limits - Kruopis, J.; Vaišvila, A. (Elektronika ir Elektrotechnika, 2005)
The increase of the sample size necessary for acceptance of the correct decisions at transition from quantitative measurements of parameters to alternative attributes is investigated. The recommendation to introduce more rigid control limits for increase infomativeness of measurements is given. The recommendation is applied in a task of the final sampling control of products. Ill. 2, bibl. 3 (in Lithuanian; summaries in Lithuanian, Russian, English).